Neutrophil extracellular traps and citrullinated fibrinogen contribute to injury in a porcine model of limb ischemia and reperfusion - Zollet, Valentina; Arenas Hoyos, Isabel; Hirsiger, Stefanie; Brahim, Bilal Ben; Petrucci, Maria Francesca; Casoni, Daniela; Wang, Junhua; Spirig, Rolf; Nettelbeck, Kay; Garcia, Luisana; Fuest, Lena; Vögelin, Esther; et al. (Frontiers in Immunology, 2024)
Background: Ischemia/reperfusion injury (IRI) is a complex pathological process, triggered by the restoration of blood flow following an interrupted blood supply. While restoring the blood flow is the only option to salvage the ischemic tissue, reperfusion after a prolonged period of ischemia initiates IRI, triggering a cascade of inflammatory responses ultimately leading to neutrophil recruitment to the inflamed tissue, where they release neutrophil extracellular traps (NETs). NETs are web-like structures of decondensed chromatin and neutrophilic proteins, including peptidyl-arginine deiminase 2 and 4 (PAD2, PAD4) that, once outside, can citrullinate plasma proteins, irreversibly changing their conformation and potentially their function. While the involvement of NETs in IRI is known mainly from rodent models, we aimed to determine the effect of NET formation and especially PADs-mediated extracellular protein citrullination in a porcine model of limb IRI. Methods: We conducted our study on amputated pig forelimbs exposed to 1 h or 9 h of ischemia and then reperfused in vivo for 12 h. Limb weight, edema formation, compartmental pressure were measured, and skeletal muscle was analyzed by immunofluorescence (TUNEL assay and dystrophin staining) to evaluate tissue damage. Fibrin tissue deposition, complement deposition and NETs were investigated by immunofluorescence. Citrullinated plasma proteins were immunoprecipitated and citrullinated fibrinogen was identified in the plasma by Western blot and in the tissue by immunofluorescence and Western blot. Results: Our data consolidate the involvement of NETs in a porcine model of limb IRI, correlating their contribution to damage extension with the duration of the ischemic time. We found a massive infiltration of NETs in the group subjected to 9 h ischemia compared to the 1 h and citrullinated fibrinogen levels, in plasma and tissue, were higher in 9 h ischemia group. We propose fibrinogen citrullination as one of the mechanisms contributing to the worsening of IRI. NETs and protein citrullination represent a potential therapeutic target, but approaches are still a matter of debate. Here we open the idea of therapeutic approaches against citrullination to specifically inhibit PADs extracellularly, avoiding the downstream effects of hypercitrullination and keeping PADs and NETs intracellular regulatory functions.